Translation of 35S and of subgenomic regions of avian sarcoma virus RNA. - Purchio, A F (1977)
Rabbit antiserum monospecific for an internal structural protein, p27, of avian sarcoma viruses (ASV) was found to immunoprecipitate polypeptides with molecular weights (Mr) of 180,000 and 76,000 from cell-free reticulocyte lysates programmed by ASV 35S RNA and also from lysates of ASV-infected cells. In addition, the Mr 180,000 protein was also precipitated by antiserum raised against virion DNA polymerase, suggesting that is a product of the two genes nearest the 5' end of virion 35S RNA. We have also investigated the ability of subgenomic portions of virion RNA to program cell-free protein synthesis. A 10-12S poly(A)-containing fragment of RNA from both nondefective and transformation-defective ASV directed the synthesis of a polypeptide of Mr 29,000 immunologically unrelated to the gs antigens; 20-24S poly(A)-containing RNA from nondefective ASV directed the synthesis of a polypeptide of Mr 60,000 not found when a similar RNA preparation from transformation-defective ASV was translated, suggesting that it is the product of the ASV src gene. These results indicate that internal initiation sites for protein synthesis exist on the 35S RNA genome.